China-Africa: emerging relations - Sousa, Ivo Carneiro de; Diakite, Ansoumane Douty; Iwaloye, Ojo Olukayode (Saint Joseph Academic Press, 2011)
Keywords: Africa China Congresses; China Africa Congresses; Relations

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny O. L. (USJ Theses and Dissertations, 2022)
Macao is well known for its gaming industry. However, there are also many traditional small-to-medium enterprises which are family-owned and run. There is no doubt that social capital is one of the key competitive advantages that family businesses possess, particularly when it comes to Chinese businesses with strong family values that emphasize the importance of trustworthiness and guanxi (relationships). As opposed to other forms of capital, social capital cannot be passed from one generation to another through the will of the incumbents. So, how is social capital passed on in family businesses from one generation to the next? Based on an in-depth study of five cases of successful family businesses in Macao, this research identified the forms of social capital present in business families and the succession process of these firms. From the generalizations drawn from the five cases, a theoretical framework is proposed to understand the intergenerational transmission of social capital in Chinese family businesses
Keywords: China Macau (Special Administrative Region); Family-owned business enterprises

Spatial Analysis Techniques Using MyGeoffice®: - Negreiros, João Garrott Marques (Advances in Geospatial Technologies, 2018)

Predictive Models for Decision Support in the COVID-19 Crisis - Marques, João Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, Jose; Fong, Simon James (SpringerBriefs in Applied Sciences and Technology, 2021)
COVID-19 has hit the world unprepared, as the deadliest pandemic of the century. Governments and authorities, as leaders and decision makers fighting the virus, enormously tap into the power of artificial intelligence and its predictive models for urgent decision support. This book showcases a collection of important predictive models that used during the pandemic, and discusses and compares their efficacy and limitations. Readers from both healthcare industries and academia can gain unique insights on how predictive models were designed and applied on epidemic data. Taking COVID19 as a case study and showcasing the lessons learnt, this book will enable readers to be better prepared in the event of virus epidemics or pandemics in the future.

Computerized Systems for Diagnosis and Treatment of COVID-19 - Lobo Marques, Joao Alexandre; Fong, Simon James (Springer International Publishing, 2023)
Keywords: Artificial Intelligence; Biofeedback; Computerized Diagnostic Support; Covid-19; Signal and Image Processing

Epidemic analytics for decision supports in COVID19 crisis - Lobo Marques, Joao Alexandre; Fong, Simon (Springer, 2022)
Covid-19 has hit the world unprepared, as the deadliest pandemic of the century. Governments and authorities, as leaders and decision makers fighting against the virus, enormously tap on the power of AI and its data analytics models for urgent decision supports at the greatest efforts, ever seen from human history. This book showcases a collection of important data analytics models that were used during the epidemic, and discusses and compares their efficacy and limitations. Readers who from both healthcare industries and academia can gain unique insights on how data analytics models were designed and applied on epidemic data. Taking Covid-19 as a case study, readers especially those who are working in similar fields, would be better prepared in case a new wave of virus epidemic may arise again in the near future.

Steps of Greatness: Geopolitics of OBOR, Ed. University of Macau. - Leandro, Francisco José (University of Macau, 2018)